ARTERIAL HYPERTENSION IN RYAZAN REGION - E. A. Smirnova (Российский кардиологический журнал, 2009)
Wide prevalence of arterial hypertension (AH) and low effectiveness of AH treatment present one of the most important healthcare problems. This study was aimed at assessing the five-year dynamics of AH prevalence, risk factors, and treatment in Ryazan Region. A representative sample of the Ryazan Region population, initially examined in 2002, as a part of the Russian Epidemiological Study “EPOCHA”, was re-examined. Socio-demographic characteristics, medical history, current clinical status and pharmaceutical therapy were assessed. During the last five years, the AH prevalence increased from 36,6% to 39,3% (p=0,07). The percentage of patients taking antihypertensive medications also increased. Improvements in both quantity and quality of antihypertensive drugs taken were associated with an increase in the number of the patients with effectively treated AH.